Identification of Candidate Genes for Clubroot-Resistance in Brassica oleracea Using Quantitative Trait Loci-Sequencing - Ce, Fuquan; Mei, Jiaqin; He, Haiyan; Zhao, Yu; Hu, Wenhui; Yu, Fengqun; Li, Qinfei; Ren, Xuesong; Si, Jun; Song, Hongyuan; Qian, Wei (Frontiers in Plant Science, 2021)
Clubroot caused by Plasmodiophora brassicae is a devastating disease of cabbage (Brassica oleracea). To identify quantitative trait loci (QTLs) for clubroot resistance (CR) in B. oleracea, genomic resequencing was carried out in two sets of extreme pools, group I and group II, which were constructed separately from 110 and 74 F2 cloned-lines derived from cross between clubroot-resistant cabbage ‘GZ87’ (against race 4) and susceptible cabbage ‘263’. Based on the QTL-Seq analysis of group I and group II, three QTLs (qCRc7-2, qCRc7-3, qCRc7-4) were determined on the C07 chromosome. RNA-Seq and qRT-PCR were conducted in the extreme pools of group II before and after inoculation, and two potential candidate genes (Bol037115 and Bol042270) which exhibiting up-regulation after inoculation in the resistant pool but down-regulation in the susceptible pool were identified from the three QTLs on C07. A functional marker ‘SWU-OA’ was developed from qCRc7-4 on C07, exhibiting ~95% accuracy in identifying CR in 56 F2 lines. Our study will provide valuable information on digging resistance genes against P. brassicae and may accelerate breeding process of B. oleracea with CR.